End-user computing satisfaction (EUCS) towards computerised accounting system (CAS) in public sector: A validation of instrument - Ilias A.; Razak M.Z.A. (2023)
This paper adapts and validates instruments (i.e. accuracy, ease of use, reliability, timeliness, content, format, and satisfaction) for measuring end-user computing satisfaction (EUCS) of computerized accounting system (CAS) in government sector (responsibility centre). The research was conducted using a set of questionnaire to 90 public sector's staffs that using CAS. Descriptive analysis and factor analysis were employed in this study to measure and validate the factors contributing to end-user computing satisfaction. The finding of this study verifies that a revised instrument with some changes to the EUCS instruments is still valid in measuring user satisfaction. We found that most of the factor loading for each item is above 0.7, which support the Doll and Torkzadeh model (1988). Azleen and Zulkeflee, 2011.